Anthropometric indices of obesity as screening tools for coronary high risk among women - Ines Lessa; Francisco Pitanga (Universidade Federal de Santa Catarina, 2006)
To identify the cut-off points and furthermore to discriminate, among different obesity anthropometrics indicators, the best performing ones in predicting high coronary risk profile (HCR) among women of two different age groups. This cross-sectional study involved 577 women aged 30-74 year. The analyses used receiver-operatingcharacteristic (ROC) curves to identify and compare the statistical significance between conicity index (C index), body mass index (BMI), waist-to-hip ratio (WHR) and waist circumference (WC), and also to discriminate CHR between women in age groups of 30-49 and 50-74 years. A 95% confidence interval (CI) was used. Areas underROC curve between the several obesity indicators and HCR were statistically significant and did not differ among 30-49 year old women, while among women aged 50-74 years, only areas under ROC curve using C index and WHR with HCR showed statistical significance. Cut-off points were defined for the several obesity indicators as a screening tool among women grouped into 30-49 years and 50-74 years. In women aged 30-49 years, the obesity indicators showed the same discriminating power for HCR. However, in 50-74 year-old women, the indicators were less effective discriminators and just central obesity indicators, C index and WHR, performed well for predicting HCR. RESUMOO principal objetivo do trabalho foi Identificar os pontos de corte de diferentes indicadores antropométricos de obesidade e determinar qual apresenta maior poder para discriminar risco coronariano elevado (RCE) em mulheres de dois diferentes grupos etários. O estudo foi de corte transversal realizado em 577 mulheres, com idade entre 30-74 anos, residentes na cidade de Salvador-Ba. A análise foi feita através das curvas ROC (Receiver Operating Characteristic) para identificar e comparar a significância estatística da área sob a mesma entre o índice de conicidade (índice C), índice de massa corporal (IMC), razão circunferência cintura-quadril (RCCQ) e circunferência de cintura (CC) para discriminar RCE entre mulheres de 30-49 anos e 50-74 anos de idade. Foi utilizado intervalo de confiança a 95%. As áreas sob a curva ROC entre os diversos indicadores de obesidade e RCE são statisticamente significativas e não apresentam diferenças em mulheres de 30-49 anos. Nas mulheres de 50-74 anos, apenas as áreas sob a curva ROC entre índice C e RCCQ com RCE apresentam significado estatístico. Pontos de corte foram definidos para os diversos indicadores de obesidade como instrumento de triagem em mulheres de 30-49 anos e 50-74 anos de idade. Os resultados do estudo demonstram que entre mulheres de 30-49 anos os indicadores de obesidade apresentam igual poder discriminatório para RCE. Em mulheres de 50-74 anos, o poder discriminatório é menor sendo que apenas os indicadores de obesidade centralíndice C e RCCQ podem ser utilizados como discriminadores de RCE.